LET IT SYNCH IN: DUBBING SYNCHRONIZATION STRATEGIES FOR SWEARING WORDS IN HOME ALONE MOVIES - Fernando, Kiki Nur (UIN Raden Mas Said Surakarta, 2025)
This research aimed at finding dubbing synchronization strategies of utterances that contain swearing words in Home Alone movie. It additionally purposed to find and describe the causes of translation shifts for swearing words from English to Indonesian. The method used in this research is descriptive qualitative. In addition, the study used documentation as a data collection technique . The data of this research were the utterances spoken by the characters in Home Alone movie. This research used the typology of Hughes (1996) to identify and classify swearing words. It also applied the taxonomy of Matamala (2010) in the identification and description of dubbing synchronization strategies. It further used the classification of translation shift by Catford (1965) in the analysis of translational changes operated in swearing words. The result of theresearch showed that there were 76 swearing expressions in total. They included 60 forms for stupidity, 3 for religion, 4 for anatomy, 5 for excretion, and 4 for animal. The researcher also found 63 cases of amplification, 7 of modification, and 6 of reduction. Futhermore, the reseacher found 11 structure shifts, 25 intra-system shifts, 26 rank shifts, and 14 class shifts. Stupidity was the dominant type of swearing words uttered in the movies. Amplification was the dominant strategy used in the movies. The dominant shift was rank or unit shift. The researcher found that the translator or dubber often changed the number of syllables in order to focus on delivering the meaning.